Carbon disclosure and firm value in UK listed firms from 2018 to 2021: evidence from UK listed firms in FTSE100 index - Treethepvilai, Ketwasa (2022)
This study aims to investigate the relationship between carbon disclosure and firm value in UK listed firms from 2018 to 2021 covering the pandemic period by selecting samples from FTSE100 index. To strengthen the accuracy and reliability of the main results, the robustness test by Environment, Social and Governance (ESG) score is performed. Furthermore, this study aims to study investor’s perspective on carbon disclosure before the pandemic event compared to after the pandemic event by performing subsample test in year 2018 (before the pandemic) and 2021 (after the pandemic). Using regression analysis model, the results show that there is no relationship between carbon disclosure and firm value in UK listed firms from 2018 to 2021. Moreover, whether before the pandemic or after the pandemic, there is no relationship between carbon disclosure and firm value in UK listed firms.